Sexual violence interventions: Considerations for humanitarian settings. (July 2017) - Wells, David
Highlights: Sexual violence may cause long-term impacts on victims, their families and the community. Services to victims may be very challenging when there is ongoing violence or civil unrest. The needs of local communities should form the foundation of any proposed service delivery. Intervention may provide an opportunity to rebuild adequate services; health, social and legal. Abstract: Sexual and gender based violence may result in a range of destructive consequences to the individual, their family and the wider community. Addressing such violence and its immediate aftermath in circumstances of civil turmoil requires a timely, planned and coordinated multidisciplinary response. Such interventions need to be cognisant of, and address a range of challenges which might include economic barriers, religious and cultural divides, a dearth of respect for human rights and limited access or capacity of medical, policing and legal services. In addition to addressing the immediate humanitarian prerogatives of health and safety issues, further objectives include the provision of support and justice for victims and the goal of ending impunity for perpetrators of sexual violence. Forensic medicine and its practitioners have the potential to make significant contributions in this field.